Antibacterial efficacy of biosynthesized silver nanoparticles against Enterococcus faecalis Biofilm: An in vitro study - Kiran Rahul Halkai; Jayashree A Mudda; Vasundhara Shivanna; Vandana Rathod; Rahul Halkai (Wolters Kluwer Medknow Publications, 2018)
Aim: This study aims to evaluate the antibacterial efficacy of biosynthesized silver nanoparticles (AgNPs) produced using the fungi against Enterococcus faecalis biofilm model on root dentin. Materials and Methods: AgNPs were biosynthesized using the fungi Fusarium semitectum isolated from healthy leaves of Withania somnifera. Minimum inhibitory concentration (MIC) of AgNPs was determined by microbroth dilution method using series of dilutions. MIC dose was standardized to evaluate the antibacterial efficacy. For biofilm model, thirty root dentin blocks prepared using human extracted single-rooted teeth were inoculated with E. faecalis in Trypticase soy agar broth for 2 weeks with alternate day replenishment and randomly divided into three groups (n = 10 each) and treated as: Group I: Sterile distilled water, Group II: AgNPs, and Group III: 2% chlorhexidine gluconate (CHX) and incubated at 37°C for 24 h. Each dentin block was rinsed in saline, vortex shaken for 60 s, and serial decimal dilutions were prepared and plated on trypticase soy agar plates and incubated for 24 h followed by CFU colony counting and statistically analyzed using one-way ANOVA followed by post hoc Tukey honestly significant difference test. Results: MIC of AgNPs for E. faecalis was determined as 30 mg/ml. No significant difference was seen between AgNPs and 2% CHX when compared to the control group with mean colony counts being 2.4, 2.5, and 6.77 CFU/ml (107), respectively (P < 0.0001), against E. faecalis biofilm. Conclusion: Biosynthesized AgNPs exhibit effective antimicrobial activity against E. faecalis biofilm on root dentin. Therefore, it can be employed as antimicrobial agent for root canal disinfection.